1988
DOI: 10.1159/000111959
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Calbindin Immunoreactivity by Subpopulations of Primary Sensory Neurons in Chick Embryo Dorsal Root Ganglion Cells Grown in Coculture or Conditioned Medium

Abstract: Primary sensory neurons which innervate neuromuscular spindles in the chicken are calbindin-immunoreactive. The influence exerted by developing skeletal muscle on the expression of calbindin immunoreactivity by subpopulations of dorsal root ganglion (DRG) cells in the chick embryo was tested in vitro in coculture with myoblasts, in conditioned medium (CM) prepared from myoblasts and in control cultures of DRG cells alone. Control cultures of DRG cells grown at the 6th embryonic day (E6) did not show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…They reported that immature (E6) chick sensory neurons do not express de novo calbindin-like immunoreactivity (a subpopulation-specific marker) in vitro unless they are cocultured with peripheral tissues. Although some subpopulation types (Bossart et al, 1988) may differentiate only in response to contact with peripheral tissues, while others can arise autonomously (present results; Ernsberger and Rohrer, 1988), this apparent contradiction may be the result of differences in culture media and substrata used in the three studies.…”
Section: Subpopulations Of Sensory Neurons May Arise From Naive Neuromentioning
confidence: 59%
See 2 more Smart Citations
“…They reported that immature (E6) chick sensory neurons do not express de novo calbindin-like immunoreactivity (a subpopulation-specific marker) in vitro unless they are cocultured with peripheral tissues. Although some subpopulation types (Bossart et al, 1988) may differentiate only in response to contact with peripheral tissues, while others can arise autonomously (present results; Ernsberger and Rohrer, 1988), this apparent contradiction may be the result of differences in culture media and substrata used in the three studies.…”
Section: Subpopulations Of Sensory Neurons May Arise From Naive Neuromentioning
confidence: 59%
“…However, the neurons in that study may not all have been naive, since they were removed from the embryo only after their in vivo birthdays, and some may have been postmitotic for up to 1 day in vivo. In contrast, results inconsistent with the above conclusion were recently described by Bossart et al (1988). They reported that immature (E6) chick sensory neurons do not express de novo calbindin-like immunoreactivity (a subpopulation-specific marker) in vitro unless they are cocultured with peripheral tissues.…”
Section: Subpopulations Of Sensory Neurons May Arise From Naive Neuromentioning
confidence: 71%
See 1 more Smart Citation
“…BDNF knockout mice are born with a 30% decrement in the normal complement of lumbar DRG neurons (Ernfors et al, 1994), and mice lacking the NT-3 receptor (TrkC) have virtually no large-fibre sensory afferents of the Ia class (Klein et al, 1994). Furthermore, the expression of particular phenotypic subpopulations of DRG sensory neurons is regulated by unidentified factors derived from central and peripheral targets (Bossart et al, 1988;Philippe et al, 1988;Barakat and Droz, 1989a. b; Barakat-Walter et al, 1991;Duc et al, 1991).…”
Section: Introductionmentioning
confidence: 99%